A retrospective study of feline lower urinary tract disease at University Veterinary Hospital, Universiti Putra Malaysia - Rosdi, Nurul Radiah (2010)
Being one of the most commonly presented diseases in University Veterinary Hospital, the study of the common criteria that predispose a cat to feline lower urinary tract disease (FLUTD) is essential. Although there were two retrospective studies carried out previously at the University Veterinary Hospital on FLUTD, this study however had a value-added aspect whereby the common urinalysis findings of those affected cats were studied. Additionally, comparisons of the common predisposing criteria between this study and the previous studies were also done. In this study, medical records of FLUTD cases presented to University Veterinary Hospital, UPM from 2005 to 2008 were selected. The collected data were analysed using descriptive analysis. From this study, there was no specific trend of the occurrence of FLUTD. As the cases were tabulated according to their months of occurrence there was no specific trend as well. Intact male cats had the highest percentage being affected. Domestic Short Hair and indoor lifestyle cats were the most commonly affected. Middle-aged cats with ideal body weight commonly succumbed to the disease. Basically, most of the presented cats were fed with commercial dry food. Stranguria/dysuria was the most commonly observed clinical signs suggestive of obstructed FLUTD. As for the urinalysis findings, most cats had abnormal urine colour, neutral urine pH, 4+ RBC and 2+ WBC. The most commonly observed crystal was triple phosphate followed by amorphous urates and calcium oxalate. With this knowledge, the owners should be well informed whether their cats are at risk of getting FLUTD or not.